Pengaruh Kualitas Kerja Pengawasan Kerja dan Lingkungan Kerja terhadap Produktivitas Karyawan pada PT Premink Abadi Indonesia - Nurfadilah, Sinta; Murniadi, Murniadi (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to determine the effect of work quality, work supervision, and the work environment on employee productivity at PT Premink Abadi Indonesia. The research method used is a quantitative method with a descriptive approach, where the study population is all 145 employees of PT Premink Abadi Indonesia, using a saturated sampling technique. Data were obtained through a questionnaire with a Likert scale and analyzed using validity and reliability tests, multiple linear regression, t-tests, and F-tests with the help of SPSS version 22. The results show that partially, work quality has a significant effect on employee productivity with a calculated t value of 7.106 > t table 1.983 and a sig. 0.000 < 0.05, while work supervision has a positive but insignificant effect with a calculated t value of 1.890 < t table 1.983 and a sig. 0.062 > 0.05. The work environment significantly influences employee productivity, with a calculated t-value of 2.678 > t-table value of 1.983 and a significance level of 0.009 < 0.05. Simultaneously, these three variables have a positive and significant effect on employee productivity, with a calculated F-value of 100.118 > F-table value of 2.69 and a significance level of 0.000 < 0.05. The conclusion of this study indicates that improving work quality, effective work supervision, and a conducive work environment can collectively increase employee productivity at PT Premink Abadi Indonesia.   Keywords: Work Quality, Work Supervision, Work Environment, Productivity, Employees